Symposium 7: Designing Collaborative Learning Sessions that Promote Creative Problem Solving Using Design Patterns - Retalis, Symeon; Katsamani, Mary; Georgiakakis, Petros; Lazakidou, Georgia; Petropoulou, Ourania; Kargidis, Theodoros (Proceedings of the International Conference on Networked Learning, 2010)
Solving problems is considered as a very important learning activity in formal educational settings concerning all grades of education from primary to tertiary education. Students’ engagement in problem solving activities helps them to acquire not only knowledge and skills on a subject domain but also useful attitudes such as thinking, flexibility, creativity, and productivity which are very important to real life. As a result numerous problem solving models and creativity techniques, mostly collaborative ones, have been proposed for aiding students solve problems. These models specify the steps of a systematic process of solution-building for a given problem description. One main open research question is “how can students learn how to apply a problem solving model”? Research has demonstrated the potential of collaborative learning sessions for enhancing young children's cognitive development and learning. The scope of this paper is to show how collaborative learning flow patterns (CLFP) can help teachers to design effective interactive learning scenarios based on well defined strategies such as Jigsaw, TPS and others that can help students learn apply problem solving models and at the same time acquire higher-order thinking skills. It is argued that CLFPs are a designer friendly way to portray the coordination and the sequencing of tasks during the learning process as well as the rationale behind them. We will present a CLFP of a collaborative problem solving strategy called e-ARMA in an attempt to explain the added value of the use of CLFPs for designing learning sessions that foster the acquisition of creative problem solving skills.